Prevalence of Acute Confusional State in Elderly and Compare the Effectiveness of Non-Pharmacological and Pharmacological Measures in a Patient Visiting Tertiary Center - Subedi, Bibek (Journal of Nobel Medical College, 2026)
Background: Delirium, an acute disorder of attention and cognition, is a common, serious, costly, under-recognized and often fatal condition for seniors. Pharmacological intervention, neither for prevention nor for treatment, has been proven effective unanimously. This article reviews the current clinical practice for delirium in geriatric patients, including etiology, diagnosis, prognosis, treatment, prevention, and outcomes.Materials and Methods: A Cross-sectional descriptive study was done to recruit the individual for this study among 98 subjects diagnosed with delirium of age group 60 and above visiting Psychiatric department and inpatient ward of College of Medical Sciences Teaching Hospital for 6 months (1st October 2025-30th March 2026). Sociodemographic characteristics and confusion assessment method-long form and confusion assessment method-short Form were administered to the subjects. The data collected was entered in Microsoft excel and analysis was done using Statistical Package for Social Services 20. The result was obtained to provide an inference.Results: Data was collected from a total of 450 patients. The prevalence of delirium was found to be 21.7%. The mean age group of study was 68.04±0.7(maximum=98; minimum=60). Female of age group 60-70, unemployed, illiterate, married and residing in urban areas were most affected.Conclusion: Delirium was common in females of age group 60-70, unemployed, illiterate, married and residing in urban areas.